If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -8p = -8(-3 + -3p) + 5 -3 + -8p = (-3 * -8 + -3p * -8) + 5 -3 + -8p = (24 + 24p) + 5 Reorder the terms: -3 + -8p = 24 + 5 + 24p Combine like terms: 24 + 5 = 29 -3 + -8p = 29 + 24p Solving -3 + -8p = 29 + 24p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-24p' to each side of the equation. -3 + -8p + -24p = 29 + 24p + -24p Combine like terms: -8p + -24p = -32p -3 + -32p = 29 + 24p + -24p Combine like terms: 24p + -24p = 0 -3 + -32p = 29 + 0 -3 + -32p = 29 Add '3' to each side of the equation. -3 + 3 + -32p = 29 + 3 Combine like terms: -3 + 3 = 0 0 + -32p = 29 + 3 -32p = 29 + 3 Combine like terms: 29 + 3 = 32 -32p = 32 Divide each side by '-32'. p = -1 Simplifying p = -1
| 3x^7=839808 | | 4x+15+107=180 | | 4(3m+8)=3(1+4m) | | 7x^2-18x-40=2x-8 | | 3x^7= | | 4+5x=11+3x | | 2x+1x-8=16 | | 5x-8=1.5 | | 7t-4=10t/14 | | x^2+12x=6x-8 | | 7(5-6x)+7=-42x-1 | | 6b^2+4b-2=0 | | (8-7i)/(2-6i) | | 11.57-3n=4.67 | | 200.00+0.25=410.00 | | 2=13+0.5x | | x^2-x+1=-7 | | x^2-x+1=1 | | 6/g=42/36 | | x^2-x+1=-1 | | a-b/x=c | | Y+7=3(x-4) | | 1.5+x=0 | | 2(3x+7)=48 | | 2(3x+7)=56 | | 22+8h=-354 | | 2(3x+7)=31 | | 3=9-3f | | 1234*x+4=9876 | | sin3t=1/2 | | -x-4=11 | | u/3--20=24 |